IJCM_42A: Nutritional Assessment and Association of Malnutrition with Food Insecurity among Adolescent Females of Age 15-19 Years in an Urban Slum of Raipur City - Galhotra Abhiruchi; Das Sakthi; Shukla Arvind K (Wolters Kluwer Medknow Publications, 2024)
Background: Adolescent girls constitute about one-tenth of our country's population. They suffer the brunt of malnutrition due to increased nutritional needs; compounded by urbanization, peer and social pressure. They are food insecure either due to unavailability, lack of resources or lower priority in food allocation. The NFHS-5 revealed that in the age group of 15€"19 years, about 39.7% of girls were thin, while 5.4% were overweight or obese. Objective: To assess the nutritional status of adolescent females of age 15-19 years in the urban field practice area of the CFM department of AIIMS Raipur and to determine if malnutrition is associated with food insecurity. Methodology: A sample size of 401 was determined, using the prevalence of 46.1% malnourishment among girls aged 15-19 years from NFHS-4 data. A community-based cross-sectional study was conducted. Participants were selected using consecutive sampling method, and anthropometric measurements were taken. Food insecurity was measured using Food Insecurity Experiential Scale. Results: According to WHO BMI-for-age Z scores for adolescents, 2% had severe thinness (<-3SD), 9.7% had thinness (-3 to <-2SD), 5% were overweight (>1 to 2SD) and 1.5% were obese (>2SD). The odds of being thin (low BMI for age) were high among girls who faced moderate to severe food insecurity [OR 3.2, CI 1.5-6.8, P <0.002]. Conclusion: The high prevalence of thinness and its significant association with food insecurity as revealed in our study, calls for immediate nutritional policy interventions to make this vulnerable group, food secure.